ASNAF ZAKAT DAN PENDISTRIBUSIANNYA: TINJAUAN FIKIH DAN EKONOMI KONTEMPORER - Hambari Hambari; Arif Ali Arif; Muntaha Artalim Zaim (Kasaba, 2020)
As the third pillar of Islam, zakat should be considered as one of the main concerned areas for Muslims. Zakat is believed to be able to have an impact on society in terms of economic, educational, and social aspects. One of the indicators of the success of zakat distribution is its impact on reducing the poverty rate, empowering economic conditions, and improving the well-being of its beneficiaries. According to Quran At Taubah verse 60 and 103, the recipients of zakat fund has been determined and the payment of zakat fund should be made through transparent, trustworthy, and professional zakat institutions. This shows the importance of zakat distribution that should be in line with Islamic law as well as a formal regulation. This study, hence, attempts to examine the eight groups who are eligible to receive zakat funds from the perspectives of Islamic jurisprudence and contemporary economic analysis. This study employs a descriptive analysis method from secondary data including classical and contemporary references. This study also provides some recommendations for zakat institutions with respect to the zakat distribution programs.